Clinical Features of Visual Disturbances in Leiden Thrombophilia - E. E. Ioyleva; A. V. Zinov’eva (Oftalʹmologiâ, 2019)
The hereditary thrombophilias is a well-recognized important risk factor for a systemic and local thromboembolic events development. The case of Leiden thrombophilia family inheritance concomitant by the visual disturbances development are shown in this аrticle. Most commonly in hereditary thrombophilias, venous thrombembolias occur, arterial occlusions which have been reported in the recent literature only as individual clinical cases occur more rarely. In the European population hereditary thrombophilias are associated with a prothrombotic mutation in the coagulation factor V gene (Leiden factor) in a greater degree; herewith the risk of thrombotic complications is increasing significantly in homozygous polymorphism forms. Presence of combined mutations in several clotting factors also leads to risk of thrombembolias increase. Consequence of the Leiden mutation is a V activator resistance to the resolving action of the activated protein C which is a natural endogenous anticoagulant protein. Resistance development leads to a deceleration of V factor inactivation and to increasing of the thrombin amount. In the work presented here, development of the consistent bilateralocclusion of the central retinal artery (CRA) in a middle-aged patient with a heterozygous form of Leiden thrombophilia is the subject of interest. Along with the hereditary hemostatic system abnormality, the patient also had cardiovascular risk factors (hypertensive disease, atherosclerosis) which had a potentiating effect on the occlusion development. Taking into account the autosomal dominant nature of the Leiden mutation inheritance, the patient’s only daughter was examined; brief episodes of amaurosis fugax against the background of headaches similar to migraine were detected due to ophthalmological abnormalities. For verification of the Leiden thrombophilia diagnosis, both patients underwent molecular genetic diagnostics. Currently there are no large prospective studies showing the optimal and economically viable approach for identification of thrombophilia genetic polymorphisms in patients with retinal vascular occlusions in daily clinical experience. Possible additional risk factors for thrombembolias development, prevention services for manifest and recurrent vascular occlusions in patients with hereditary blood coagulation system abnormalities and their relatives are discussed in this article.